Non-aqueous electrolyte secondary battery

By dividing the negative electrode active material layer into regions with varying porosities and using sulfite or sulfate compounds in the electrolyte, the battery's initial cycle and high-rate performance are enhanced through stable film formation and reduced resistance.

JP7620816B2Active Publication Date: 2025-01-24PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021563875
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-13
Filing Date
2020-12-01
Publication Date
2025-01-24
Estimated Expiration
2040-12-01

AI Technical Summary

Technical Problem

In non-aqueous electrolyte secondary batteries, the porosity difference between the negative electrode surface and current collector side leads to side reactions and film formation, increasing resistance and decreasing capacity during the initial cycles due to exposure and decomposition of the non-aqueous electrolyte.

Method used

The negative electrode active material layer is divided into two regions with different porosities, where the upper layer has a higher interparticle porosity than the lower layer, and the electrolyte includes sulfite or sulfate compounds to form a stable, low-resistance film on the surface.

Benefits of technology

This configuration improves initial cycle characteristics and high-rate performance by preventing film destruction and exposure of the active surface, maintaining capacity and reducing resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007620816000004
    Figure 0007620816000004
  • Figure 0007620816000005
    Figure 0007620816000005
  • Figure 0007620816000006
    Figure 0007620816000006
Patent Text Reader

Abstract

This non-aqueous electrolyte secondary battery is provided with a positive electrode, a negative electrode, and a non-aqueous electrolyte. The negative electrode is provided with a negative electrode current collector, and a negative electrode active material layer supported on the negative electrode current collector. When the negative electrode active material layer is divided into two layers, a first region and a second region which have the same thickness, the second region is closer to the negative electrode current collector than the first region, and the first region and the second region each include graphite particles. A ratio P1 / P2 of the interparticle porosity P1 of the first region to the interparticle porosity P2 of the second region is more than 1. The non-aqueous electrolyte includes at least one additive selected from the group consisting of a sulfite compound and a sulfate compound.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a non-aqueous electrolyte secondary battery. [Background technology]

[0002] Non-aqueous electrolyte secondary batteries, particularly lithium ion secondary batteries, have high voltage and high energy density and are widely used as power sources for small electronic devices such as portable devices. Non-aqueous electrolyte secondary batteries include a positive electrode, a negative electrode, and a non-aqueous electrolyte. The negative electrode usually includes a negative electrode current collector and a negative electrode active material layer supported on the negative electrode current collector.

[0003] Incidentally, one method for improving the circulation of a non-aqueous electrolyte to the negative electrode active material layer is to increase the porosity of the negative electrode active material layer on the negative electrode surface side rather than on the negative electrode current collector side (for example, Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2015-037008 A Summary of the Invention

[0005] In the negative electrode active material layer having a larger porosity on the negative electrode surface side than on the negative electrode current collector side, the negative electrode active material and the nonaqueous electrolyte are likely to come into contact with each other to cause a side reaction, and the nonaqueous electrolyte is likely to decompose on the particle surface of the negative electrode active material to form a coating. In addition, the coating is destroyed due to the expansion and contraction of the negative electrode active material and particle cracking during charging and discharging, exposing the active surface of the negative electrode active material and contacting the nonaqueous electrolyte, and the coating is formed due to the decomposition of the nonaqueous electrolyte on the active surface. The coating formation is likely to increase the negative electrode resistance and reduce the capacity in the early stages of cycling.

[0006] In view of the above, one aspect of the present disclosure relates to a nonaqueous electrolyte secondary battery comprising: a positive electrode, a negative electrode, and a nonaqueous electrolyte; the negative electrode comprises a negative electrode current collector and a negative electrode active material layer supported on the negative electrode current collector; when the negative electrode active material layer is divided into two layers, a first region and a second region, having the same thickness, the second region is closer to the negative electrode current collector than the first region; the first region and the second region each contain graphite particles; a ratio P1 / P2 of an interparticle porosity P1 of the first region to an interparticle porosity P2 of the second region is greater than 1; and the nonaqueous electrolyte contains at least one additive selected from the group consisting of sulfite compounds and sulfate compounds.

[0007] According to the present disclosure, a nonaqueous electrolyte secondary battery having excellent initial cycle characteristics can be obtained. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 is a diagram illustrating a cross section of a negative electrode active material layer in a nonaqueous electrolyte secondary battery according to one embodiment of the present disclosure. [Diagram 2] FIG. 2 is a diagram illustrating a cross section of a graphite particle used in a nonaqueous electrolyte secondary battery according to an embodiment of the present disclosure. [Diagram 3] FIG. 3 is a schematic perspective view, with a portion cut away, of a nonaqueous electrolyte secondary battery according to one embodiment of the present disclosure. [Figure 4] FIG. 4 is a schematic cross-sectional view of a negative electrode used in the nonaqueous electrolyte secondary battery of FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] A nonaqueous electrolyte secondary battery according to an embodiment of the present disclosure includes a positive electrode, a negative electrode, and a nonaqueous electrolyte. The negative electrode includes a negative electrode current collector and a negative electrode active material layer supported on the negative electrode current collector. When the negative electrode active material layer is divided into two layers, a first region and a second region, having the same thickness, the second region is closer to the negative electrode current collector than the first region, and each of the first region and the second region contains graphite particles as the negative electrode active material. The ratio P1 / P2 of the interparticle porosity P1 of the first region to the interparticle porosity P2 of the second region is greater than 1. The nonaqueous electrolyte includes at least one additive selected from the group consisting of sulfite compounds and sulfate compounds.

[0010] By using a negative electrode active material layer having a larger interparticle porosity in the first region (upper layer) than in the second region (i.e., the lower layer based on the current collector), the liquid circulation of the nonaqueous electrolyte to the negative electrode active material layer is improved. The improved liquid circulation facilitates the progress of the battery reaction, and improves, for example, high-rate characteristics (for example, cycle characteristics when charging at a high rate).

[0011] The additive can form a low-resistance and stable coating (solid electrolyte interphase) on the surface of the negative electrode active material. Since the additive has a relatively high reduction potential, a low-resistance coating derived from the additive is preferentially formed on the surface of the negative electrode active material in the negative electrode active material layer (particularly the upper layer) where the negative electrode active material and the nonaqueous electrolyte are likely to come into contact with each other at the beginning of the cycle.

[0012] In addition, the coating derived from the additive has excellent durability (strength) and is also excellent in compliance (flexibility) with the expansion and contraction of the negative electrode active material. Therefore, the destruction of the coating caused by the expansion and contraction of the negative electrode active material and particle cracking during charging and discharging is suppressed. By suppressing the destruction of the coating, the exposure of the active surface of the negative electrode active material is suppressed, and the contact between the active surface and the nonaqueous electrolyte and the excessive formation of the coating (repair of the coating) caused by the contact are suppressed.

[0013] From the above, the capacity decrease in the initial cycle due to the increase in the negative electrode resistance accompanying the formation of the coating is suppressed. The initial cycle is, for example, in the range of several cycles or more and 30 cycles or less. In addition, repeated destruction and repair of the coating accompanying repeated charging and discharging is suppressed, and the medium-term cycle characteristics are also improved. The medium-term cycle is, for example, in the range of more than 30 cycles and 300 cycles or less.

[0014] From the viewpoint of forming a good quality coating, the non-aqueous electrolyte may contain vinylene carbonate (VC), fluoroethylene carbonate (FEC), or the like, in addition to the above additives.

[0015] In general, some components of the non-aqueous electrolyte are used for initial film formation and also for repairing the film destroyed by repeated charging and discharging. Examples of such components include VC and FEC. However, when the film is easily damaged due to expansion and contraction of the negative electrode active material, the amount of components used for repairing the film increases, which increases the film resistance and may deteriorate the initial cycle characteristics.

[0016] In contrast, in the present disclosure, the additive is included in the non-aqueous electrolyte. Since the additive has a high reduction potential, a coating derived from the additive is preferentially formed. The coating derived from other components is mainly formed on the coating derived from the additive and can function as a part of the coating. Since the coating derived from the additive is difficult to break, repair of the coating by other components is suppressed, and a decrease in initial cycle characteristics due to an increase in coating resistance accompanying the repair of the coating is suppressed.

[0017] At least one of a sulfite compound and a sulfate compound is used as an additive for the non-aqueous electrolyte. The sulfite compound is an organic compound (sulfurous acid diester compound) having a structure of -OS(=O)-O- in the molecule. The sulfate compound is an organic compound (sulfuric acid diester compound) having a structure of -OS(=O)2-O- in the molecule. The molecular structure of the sulfite compound and the sulfate compound may be linear or cyclic.

[0018] The additive is, for example, a compound represented by RA-R'. A is -OS(=O)-O- or -OS(=O)2-O-. R and R' are each independently a hydrocarbon group. R and R' may be bonded to form a ring. The hydrocarbon group includes an alkyl group, an alkenyl group, an aryl group, and the like. The hydrocarbon group may be linear or branched. The alkyl group includes a methyl group, an ethyl group, an n-propyl group, an isopropyl group, and the like. The alkenyl group includes a vinyl group, a 1-propenyl group, a 2-propenyl group, and the like. The aryl group includes a phenyl group, a benzyl group, and the like. At least one hydrogen atom of the hydrocarbon group may be substituted with a halogen atom or the like. From the viewpoint of ensuring good viscosity and improving solubility of the nonaqueous electrolyte, the hydrocarbon group is preferably an alkyl group having 1 to 5 carbon atoms, more preferably an alkyl group having 1 to 3 carbon atoms.

[0019] An example of the cyclic sulfite compound is a compound represented by the following general formula (1).

[0020] [ka]

[0021] R in general formula (1) 1 ~R 4 are each independently a hydrogen atom or a substituent. The substituent includes a halogen atom, a hydrocarbon group, a hydroxyl group, an amino group, an ester group, and the like.

[0022] The hydrocarbon group includes an alkyl group and an alkenyl group. The alkyl group and the alkenyl group may be linear or branched. The alkyl group includes a methyl group, an ethyl group, an n-propyl group, an isopropyl group, and the like. The alkenyl group includes a vinyl group, a 1-propenyl group, a 2-propenyl group, and the like. At least one hydrogen atom of the hydrocarbon group may be substituted with a halogen atom or the like. From the viewpoint of ensuring good viscosity and improving solubility of the nonaqueous electrolyte, the hydrocarbon group is preferably an alkyl group having 1 to 5 carbon atoms, more preferably an alkyl group having 1 to 3 carbon atoms.

[0023] In the general formula (1), n ​​is R 3 and R 4 The number of repeating methylene groups having the formula: n is an integer of 1 to 3. When n is 2 or 3, the number of repeating methylene groups having the formula: 3 and R 4 may be the same as or different from each other.

[0024] Specific examples of the compound represented by general formula (1) include ethylene sulfite (ES), 1,3-propylene sulfite, 1,2-propylene sulfite, 1,3-butylene sulfite, 1,2-butylene sulfite, 1,2-pentene sulfite, fluoroethylene sulfite, 1,2-difluoroethylene sulfite, and vinylethylene sulfite.

[0025] Examples of chain sulfite compounds include diethyl sulfite, dimethyl sulfite, dipropyl sulfite, dibutyl sulfite, dipropargyl sulfite, bis(fluoroethyl) sulfite, bis(difluoroethyl) sulfite, bis(trifluoroethyl) sulfite, bis(trimethylsilyl) sulfite, and bis(2-propenyl) sulfite.

[0026] Among them, ES is preferable as the sulfite compound from the viewpoint of improving the initial cycle characteristics and high rate characteristics. ES has small steric hindrance of the molecule, and the reaction of forming the ES-derived film on the surface of the negative electrode active material tends to proceed smoothly. In addition, ES has a moderately high reduction potential and a moderately low viscosity, which are also advantageous for forming the ES-derived film. The sulfite compound may be used alone or in combination of two or more kinds.

[0027] An example of the cyclic sulfate compound is a compound represented by the following general formula (2).

[0028] [ka]

[0029] R in general formula (2) 5 ~R 8 and n is R in general formula (1). 1 ~R 4 and similar to n.

[0030] Specific examples of the compound represented by general formula (2) include ethylene sulfate (DTD), 1,3-propylene sulfate, 1,2-propylene sulfate, 1,3-butylene sulfate, 1,2-butylene sulfate, 1,2-pentene sulfate, fluoroethylene sulfate, 1,2-difluoroethylene sulfate, and vinylethylene sulfate.

[0031] Examples of chain sulfate compounds include diethyl sulfate, dimethyl sulfate, dipropyl sulfate, dibutyl sulfate, dipropargyl sulfate, bis(fluoroethyl) sulfate, bis(difluoroethyl) sulfate, bis(trifluoroethyl) sulfate, bis(trimethylsilyl) sulfate, and bis(2-propenyl) sulfate.

[0032] From the viewpoint of improving initial cycle characteristics and high-rate characteristics, DTD is the most preferable sulfate compound. DTD has small steric hindrance of the molecule, and the reaction of forming a film derived from DTD on the surface of the negative electrode active material tends to proceed smoothly. In addition, DTD has a moderately high reduction potential and a moderately low viscosity, which are also advantageous for forming a film derived from DTD. The sulfate compound may be used alone or in combination of two or more types.

[0033] The content of the additive in the nonaqueous electrolyte (mass ratio to the entire nonaqueous electrolyte) is preferably 2% by mass or less, more preferably 0.5% by mass or more and 2% by mass or less, and even more preferably 0.5% by mass or more and 1.5% by mass or less. Before the first charge of the battery (or before the electrolyte is poured into the battery), the content of the additive in the nonaqueous electrolyte is preferably within the above range. When the content of the additive in the nonaqueous electrolyte is 2% by mass or less, a coating derived from the additive is easily formed appropriately, and the coating resistance is easily reduced. In addition, when the content of the additive in the nonaqueous electrolyte is 2% by mass or less, the nonaqueous electrolyte can be easily adjusted to an appropriate viscosity. When the content of the additive in the nonaqueous electrolyte is 0.5% by mass or more, a coating derived from the additive is easily formed sufficiently. The content of the additive in the nonaqueous electrolyte is determined, for example, by gas chromatography mass spectrometry (GC / MS).

[0034] During the charging and discharging process, at least a part of the additive is decomposed and used to form a coating. Therefore, in a battery after charging and discharging (for example, an initial battery that has been charged and discharged several times), the content of the additive in the nonaqueous electrolyte may be less than 2 mass%. When the content of the additive when the nonaqueous electrolyte is prepared is 2 mass% or less, the content of the additive in the nonaqueous electrolyte in a battery after the first charge (for example, a commercially available battery) may be, for example, 100 ppm or less. The content of the additive contained in the nonaqueous electrolyte taken out from the battery may be a trace amount close to the detection limit. If the presence of the additive can be confirmed, the corresponding improvement effect on the initial cycle characteristics and high rate characteristics can be recognized.

[0035] The ratio P1 / P2 of the interparticle porosity P1 of the first region to the interparticle porosity P2 of the second region is greater than 1. By making the interparticle porosity greater in the first region than in the second region, the flow of the nonaqueous electrolyte to the negative electrode active material layer is improved, the utilization rate of the negative electrode active material in the negative electrode active material layer is increased, and the high-rate characteristics are particularly likely to be improved. By making the interparticle porosity smaller in the second region than in the first region, the adhesion between the negative electrode active material layer and the negative electrode current collector is increased, and the deterioration of the cycle characteristics due to the deterioration of the adhesion between the negative electrode active material layer and the negative electrode current collector is suppressed.

[0036] Here, the interparticle porosity P1 of the first region means the ratio of the area SP1 of the gaps between the negative electrode active material particles in the first region to the area SA1 of the first region in a cross section of the first region (cross section in the thickness direction of the negative electrode active material layer), and is calculated by (SP1 / SA1) × 100. The area SA1 of the first region means the combined area of ​​the negative electrode active material particles and the gaps between the negative electrode active material particles in the first region.

[0037] The interparticle porosity P2 of the second region means the ratio of the area SP2 of the gaps between the negative electrode active material particles in the second region to the area SA2 of the second region in a cross section of the second region (cross section in the thickness direction of the negative electrode active material layer), and is calculated by (SP2 / SA2) × 100. The area SA2 of the second region means the combined area of ​​the negative electrode active material particles and the gaps between the negative electrode active material particles in the second region.

[0038] The negative electrode active material particles in the first and second regions contain at least graphite particles, and may further contain Si-based particles. When the first and second regions contain components (such as a binder) other than the negative electrode active material particles, the amount of the other components is very small relative to the negative electrode active material particles, and is at a negligible level.

[0039] P1 / P2 is preferably 1.1 or more and 2.0 or less, more preferably 1.1 or more and 1.5 or less. When P1 / P2 is 1.1 or more, high-rate characteristics are likely to be improved. When P1 / P2 is 2.0 or less, it is advantageous in terms of ensuring the strength of the negative electrode active material layer (negative electrode surface side) and the negative electrode capacity (filling amount of negative electrode active material). In the first region, contact between the negative electrode active material particles is sufficiently ensured, and a conductive network between the negative electrode active material particles is sufficiently ensured.

[0040] The above P1 / P2 can be determined by the following method.

[0041] A battery after the initial cycle (for example, a battery that has been charged and discharged several to several dozen times) is disassembled, a part of the negative electrode is cut out, and an ion milling device or the like is used to obtain a cross-section of a sample of the negative electrode active material layer. For example, an "IM4000PLUS" manufactured by Hitachi High-Tech Corporation can be used as the ion milling device. A scanning electron microscope (SEM) is used to take a backscattered electron image (magnification: 800 times) of the cross-section of the sample to obtain a cross-sectional image of the sample. The cross-sectional image of the sample obtained above is imported into a computer and divided into a first region and a second region. The cross-sectional image of the first region and the cross-sectional image of the second region are each subjected to a binarization process.

[0042] For example, the image analysis software "ImageJ" manufactured by the National Institutes of Health can be used for the binarization of the cross-sectional image of the sample. In the binarization, the negative electrode active material particles (including the internal voids of the particles) are shown in white, and the voids between the particles (including the external voids of the particles) are shown in black in the cross-sectional image of the sample. When the negative electrode active material particles have minute voids with a maximum diameter of 3 μm or less, it may be difficult to distinguish between internal and external voids in image analysis, so voids with a maximum diameter of 3 μm or less are regarded as internal voids. Note that components other than the negative electrode active material particles (e.g. SBR and CMC) are also shown in white, but the amount is so small that it can be ignored.

[0043] FIG. 1 is a diagram illustrating a cross section of a negative electrode active material layer of a nonaqueous electrolyte secondary battery according to one embodiment of the present disclosure, and is an enlarged view of a portion of the cross section in the thickness direction of the negative electrode active material layer.

[0044] The negative electrode active material layer 30 has negative electrode active material particles 31 and voids 32 between the negative electrode active material particles 31. The negative electrode active material particles 31 are represented in white, and the voids 32 (hatched areas in FIG. 1 ) are represented in black by the binarization process. When the negative electrode active material particles 31 are graphite particles, the negative electrode active material particles 31 may have voids (internal voids 33) closed within the particles 31. The internal voids 33 are regarded as part of the negative electrode active material particles 31, and are represented in white by the binarization process. The negative electrode active material particles 31 may have voids (external voids 34) connected to the external space of the particles 31. The external voids 34 are regarded as part of the voids between the particles 31, and are represented in black by the binarization process.

[0045] Using the binarized cross-sectional image of the first region, the area SW1 occupied by white and the area SB1 occupied by black in the first region are calculated. The sum of area SW1 and area SB1 is set to the area SA1 of the first region. Area SB1 is set to the area SP1 of the void in the first region.

[0046] Using the binarized cross-sectional image of the second region, the area SW2 occupied by white and the area SB2 occupied by black in the second region are calculated. The sum of areas SW2 and SB2 is set as the area SA2 of the second region. Area SB2 is set as the area SP2 of the void in the second region.

[0047] Using the area SA1 of the first region, the area SP1 of the void in the first region, the area SA2 of the second region, and the area SP2 of the void in the second region, P1 / P2 is calculated from the following formula.

[0048] P1 / P2=(SP1 / SA1) / (SP2 / SA2) From the viewpoint of increasing capacity, the ratio D1 / D2 of the packing density D1 of the first region to the packing density D2 of the second region is preferably 0.9 or more and 1.1 or less. Here, the packing density D1 of the first region means the mass per unit volume of the first region. The packing density D2 of the second region means the mass per unit volume of the second region.

[0049] From the viewpoint of increasing capacity, the first region and the second region are each set to 1.3 g / cm3 More than 2.0g / cm 3 It is preferred to have a packing density of:

[0050] The packing density D1 of the first region and the packing density D2 of the second region can be determined by the following method.

[0051] Using a cross-sectional image of the sample obtained in the process of determining the interparticle porosity, the thickness T of the negative electrode active material layer is determined, and T / 2 is defined as the thickness of the first region and the thickness of the second region. A part of the negative electrode in which the negative electrode active material layer is supported on a sheet-like negative electrode current collector is cut out, the first region is scraped off from the negative electrode, and the mass W2 and area A2 of the second region remaining on the negative electrode current collector are determined. The area A2 is the area of ​​the second region when viewed from the thickness direction. Using the mass W2, area A2, and thickness T / 2 of the second region, the packing density D2 (g / cm) of the second region is calculated from the following formula: 3 ) is calculated.

[0052] Packing density of the second region D2 = W2 / (A2 × T / 2) Separately, a part of the negative electrode is cut out, adhesive tape is applied onto the negative electrode active material layer (first region), and the negative electrode active material layer is peeled off from the sheet-like negative electrode current collector. The second region of the negative electrode active material layer transferred to the adhesive tape is scraped off, and the mass W1 and area A1 of the first region remaining on the tape are determined. The area A1 is the area of ​​the first region when viewed from the thickness direction. Using the mass W1, area A1, and thickness T / 2 of the first region, the packing density D1 (g / cm) of the first region is calculated from the following formula: 3 ) is calculated.

[0053] Packing density of the first region D1 = W1 / (A1 × T / 2) From the viewpoint of easily improving cycle characteristics and high-rate characteristics, it is preferable that the graphite particles include graphite particles A having an internal porosity of 5% or less and graphite particles B having an internal porosity of more than 5%, and that the graphite particles A are contained in the first region more than in the second region. In this case, it is easy to make P1 / P2 larger than 1 while suppressing a decrease in the packing density of the first region. The ratio of the content WC2 of the graphite particles A in the second region to the content WC1 of the graphite particles A in the first region: WC2 / WC1, is preferably 0 or more and less than 1. WC2 / WC1 may be 0 or more and 0.75 or less, or may be 0 or more and 0.5 or less.

[0054] The internal porosity of graphite particles A may be 1% or more and 5% or less, or 3% or more and 5% or less. The internal porosity of graphite particles B may be 8% or more and 20% or less, or 12% or more and 18% or less. When the internal porosity of graphite particles A and graphite particles B is within the above range, the initial cycle characteristics and high rate characteristics are likely to be improved, which is also advantageous for achieving a high capacity.

[0055] Here, FIG. 2 is a diagram that illustrates a cross section of a graphite particle used in a nonaqueous electrolyte secondary battery according to an embodiment of the present disclosure.

[0056] The graphite particle 20 has an internal void 21 closed inside the graphite particle 20, and an external void 22 connected to the space outside the graphite particle 20. The external void 22 is included in the void between the negative electrode active material particles in the negative electrode active material layer.

[0057] Here, the internal void ratio of graphite particle 20 means the ratio of the area SC2 of internal void 21 to the area SC1 of graphite particle 20 in the cross section of graphite particle 20, and is calculated by (SC2 / SC1) × 100. The area SC1 of graphite particle 20 is the area of ​​the region surrounded by the outer periphery of graphite particle 20, and means the combined area of ​​the hatched portion in Fig. 2 and internal void 21. When multiple internal voids 21 are present, the area SC2 of internal void 21 means the combined area of ​​the multiple internal voids 21.

[0058] By including more graphite particles A, which have a high intraparticle density, in the first region than in the second region, the interparticle porosity can be increased in the first region than in the second region. For example, the first and second regions may include the same amount of graphite particles, and the proportion of graphite particles A in the graphite particles may be higher in the first region than in the second region. Since graphite particles A have a high intraparticle density, it is possible to increase the interparticle porosity in the first region while suppressing a decrease in packing density. For example, the above D1 / D2 can be controlled within a range of 0.9 to 1.1, and the interparticle porosity can be increased to 1.3 g / cm in both the first and second regions. 3 More than 2.0g / cm 3 A high packing density can be obtained:

[0059] The graphite particles A may be contained in the first region and the second region, or may be contained only in the first region. The graphite particles B may be contained in the first region and the second region, or may be contained only in the second region. From the viewpoint of the capacity balance in the negative electrode active material layer, it is preferable that the total mass of the graphite particles A and the graphite particles B contained in the first region is approximately the same as the total mass of the first region and the second region contained in the second region.

[0060] In the first region, the proportion of graphite particles A in the total of graphite particles A and graphite particles B is preferably 20% by mass or more and 100% by mass or less, and more preferably 50% by mass or more and 100% by mass or less. In the second region, the proportion of graphite particles B in the total of graphite particles A and graphite particles B is preferably 90% by mass or more and 100% by mass or less, and more preferably 100% by mass.

[0061] The internal porosity of the graphite particles can be determined by the following method.

[0062] An initial battery (an unused battery or a battery that has been charged and discharged several times) is disassembled, the negative electrode is removed, a part of the negative electrode is sampled, and an ion milling device or the like is used to obtain a cross-section of the negative electrode active material layer. For example, a Hitachi High-Technologies Corporation model "IM4000PLUS" can be used as the ion milling device. A plurality of graphite particles may be embedded in epoxy resin or the like, and polished to obtain a cross-section of the plurality of graphite particles, which may be used as the cross-section of the sample. A scanning electron microscope (SEM) is used to take a backscattered electron image (magnification: 3,000 to 5,000 times) of the cross-section of the sample to obtain a cross-section image of the sample. The cross-section image of the sample obtained above is imported into a computer and binarized. For example, the image analysis software "ImageJ" manufactured by the National Institutes of Health can be used to binarize the cross-section image. In the binarization process, the negative electrode active material particles (including voids inside the particles) are displayed in black in the cross-section image, and the voids between the particles are displayed in white.

[0063] Using the binarized cross-sectional image, graphite particles with a maximum diameter of 5 μm or more and 50 μm or less are arbitrarily selected. The area SC1 of the graphite particles and the area SC2 of the internal voids of the graphite particles are calculated. Note that, in image analysis, it may be difficult to distinguish whether a minute void with a maximum diameter of 3 μm or less is an internal void or an external void. For this reason, voids with a maximum diameter of 3 μm or less are regarded as internal voids. Furthermore, when the negative electrode active material particles contain graphite particles and Si-based particles, the graphite particles and Si-based particles can be distinguished from each other using the SEM image (backscattered electron image) of the cross-section of the sample obtained above. In the SEM image of the cross-section of the sample, the graphite particles are black, while the Si-based particles (SiO x The particles, etc., are gray in color.

[0064] The internal porosity (%) of the graphite particle is calculated from the area SC1 of the graphite particle and the area SC2 of the internal void obtained above according to the following formula.

[0065] Internal porosity of graphite particle = (SC2 / SC1) x 100 Graphite particles with an internal porosity of 5% or less are called graphite particles A, and graphite particles with an internal porosity of more than 5% are called graphite particles B. Calculate the average internal porosity of 10 graphite particles A. Calculate the average internal porosity of 10 graphite particles B.

[0066] The graphite particles A can be produced, for example, by the following method.

[0067] The main raw material, coke (precursor), is pulverized, a binder is added to the pulverized material, and the pulverized material is aggregated. The average particle size (D50) of the pulverized coke is, for example, 12 μm or more and 20 μm or less. In this specification, the average particle size (D50) means a particle size (volume average particle size) at which the volume integrated value is 50% in the particle size distribution obtained by the laser diffraction scattering method. The obtained aggregate is fired, graphitized, and sieved to obtain graphite particles A of a desired size. The firing temperature is, for example, 2600° C. or more, and may be 2600° C. or more and 3000° C. or less.

[0068] The internal porosity of the graphite particles A can be controlled, for example, by the particle size of the crushed coke or the aggregate. For example, to reduce the internal porosity, the particle size of the crushed coke or the aggregate may be increased. In addition, when a part of the binder contained in the aggregate volatilizes during firing, the internal porosity may be controlled by the amount of binder added. An example of such a binder is pitch.

[0069] The graphite particles B can be produced, for example, by the following method.

[0070] The main raw material, coke (precursor), is pulverized, a binder is added to the pulverized material, and the pulverized material is agglomerated. The average particle size (D50) of the pulverized coke is, for example, 12 μm or more and 20 μm or less. The resulting agglomerate is pressurized to obtain a block-shaped compact, which is then fired and graphitized. The firing temperature is, for example, 2600° C. or more, and may be 2600° C. or more and 3000° C. or less. The density of the compact is, for example, 1.6 g / cm 3 More than 1.9g / cm 3The obtained block-shaped graphitized product is crushed and sieved to obtain graphite particles B of a desired size.

[0071] The internal porosity of the graphite particles B may be controlled by the particle size of the crushed coke or aggregates. When a volatile component is added to a block-shaped compact during firing, the internal porosity of the graphite particles B may be controlled by the amount of the volatile component added to the block-shaped compact. When a part of the binder added to the crushed coke volatilizes during firing, the binder may also serve as the volatile component added to the compact. In this case, the internal porosity may be controlled by the amount of the binder added. An example of such a binder is pitch. For example, the amount of pitch added to the crushed material during the process of producing the graphite particles B may be made larger than the amount of pitch added to the crushed material during the process of producing the graphite particles A, thereby producing graphite particles B having a larger internal porosity than the graphite particles A.

[0072] Hereinafter, an example of a method for producing a negative electrode having a negative electrode active material layer in which the interparticle porosity is greater in the first region than in the second region will be described.

[0073] A first negative electrode slurry and a second negative electrode slurry are prepared. At this time, the first negative electrode slurry may contain more graphite particles A than the second negative electrode slurry. The first negative electrode slurry may contain graphite particles A, and the second negative electrode slurry may contain graphite particles B. The second negative electrode slurry is used to form a second negative electrode active material layer, and the first negative electrode slurry is used to form a first negative electrode active material layer having a larger internal porosity than the second negative electrode active material layer. Specifically, the second negative electrode slurry is applied onto the negative electrode current collector, the second coating is dried, the first negative electrode slurry is applied onto the second coating, and the first coating is dried. The laminate of the first coating and the second coating after drying may be rolled. In this manner, the second negative electrode active material layer and the first negative electrode active material layer are formed in this order on the negative electrode current collector. The second coating may be dried at the same time as the first coating after the first negative electrode slurry is applied onto the second coating. The first negative electrode active material layer and the second negative electrode active material layer may have the same thickness. The value of P1 / P2 may be controlled by changing the ratio T1 / T2 of the thickness T2 of the second negative electrode active material layer to the thickness T1 of the first negative electrode active material layer.

[0074] Another example of a method for producing a negative electrode having a negative electrode active material layer in which the interparticle porosity is greater in the first region than in the second region will be described below.

[0075] A negative electrode slurry is applied onto a negative electrode current collector, the coating is dried, and the coating is rolled at a second pressure to form a second negative electrode active material layer, and the same negative electrode slurry as above is applied onto the second negative electrode active material layer, the coating is dried, and the coating is rolled at a first pressure lower than the second pressure to form a first negative electrode active material layer on the second negative electrode active material layer, the first negative electrode active material layer having a larger interparticle porosity than the second negative electrode active material layer. In this case, the second negative electrode active material layer is more likely to have a higher packing density than the first negative electrode active material layer.

[0076] The negative electrode active material layer may be formed by stacking three or more layers having different interparticle porosities so that the interparticle porosity increases from the negative electrode current collector side to the negative electrode surface side. Such a negative electrode active material layer can be formed, for example, by preparing three or more types of negative electrode slurries having different contents of graphite particles A, and applying the negative electrode slurries to the negative electrode current collector in order starting from the negative electrode slurry having the smallest content of graphite particles A. When such a negative electrode active material layer is divided into a first region and a second region, the first region has a larger interparticle porosity than the second region.

[0077] Next, the nonaqueous electrolyte secondary battery according to the embodiment of the present disclosure will be described in detail. The nonaqueous electrolyte secondary battery includes, for example, a negative electrode, a positive electrode, and a nonaqueous electrolyte as described below.

[0078] [Negative electrode] The negative electrode comprises a negative electrode current collector and a negative electrode active material layer supported on the surface of the negative electrode current collector. The negative electrode active material layer can be formed, for example, by applying a negative electrode slurry in which a negative electrode mixture is dispersed in a dispersion medium to the surface of the negative electrode current collector and drying it. The coating film after drying may be rolled as necessary. The negative electrode active material layer may be formed on one surface of the sheet-shaped negative electrode current collector or on both surfaces. The negative electrode mixture contains a negative electrode active material as an essential component, and may contain a binder, a conductive agent, a thickener, etc. as optional components.

[0079] The negative electrode active material contains at least graphite particles. As the graphite particles, particles such as natural graphite and artificial graphite can be used. From the viewpoint of easy control of the internal porosity, artificial graphite particles are preferable. The graphite particles may partially contain amorphous carbon, graphitizable carbon (soft carbon), and non-graphitizable carbon (hard carbon).

[0080] Graphite is a carbon material with a developed graphite crystal structure. The interplanar spacing d002 of the (002) plane of the graphite particles measured by X-ray diffraction may be, for example, 0.340 nm or less, or 0.3354 nm or more and 0.340 nm or less. The crystallite size Lc(002) of the graphite particles measured by X-ray diffraction may be, for example, 5 nm or more, 5 nm or more and 300 nm or less, or 10 nm or more and 200 nm or less. The crystallite size Lc(002) is measured by, for example, the Scherrer method. When the interplanar spacing d002 of the (002) plane of the graphite particles and the crystallite size Lc(002) are within the above ranges, a high capacity is easily obtained.

[0081] The average particle size (D50) of the graphite particles is, for example, 1 μm or more and 30 μm or less. In this specification, the average particle size (D50) means the particle size (volume average particle size) at which the volume accumulated value is 50% in the particle size distribution measured by the laser diffraction scattering method. For example, the "LA-750" manufactured by HORIBA Co., Ltd. can be used as the measuring device.

[0082] From the viewpoint of increasing capacity, the negative electrode active material may contain Si-based particles. The Si-based particles are preferably contained in the first region and the second region. The average particle size (D50) of the Si-based particles is, for example, 1 μm or more and 25 μm or less. Examples of the Si-based particles include silicon simple particles, silicon-containing alloy particles, and silicon-containing composite particles. The silicon-containing alloy particles include, for example, silicon (Si) and at least one element selected from the group consisting of tin (Sn), nickel (Ni), iron (Fe), copper (Cu), titanium (Ti), manganese (Mn), and aluminum (Al).

[0083] The composite particles containing silicon may include a lithium ion conductive phase (matrix phase) and silicon particles (fine Si phase) dispersed in the phase. Examples of the lithium ion conductive phase include a SiO2 phase, a silicate phase (e.g., lithium silicate phase), and a carbon phase.

[0084] The SiO2 phase is an amorphous phase containing 95% by mass or more of silicon dioxide. The SiO2 phase easily occludes lithium ions by the first charge and forms a Li4SiO4 phase. The composite particles in which silicon particles are dispersed in the SiO2 phase are represented by SiO x where x is, for example, 0.8 ≦ x ≦ 1.6. SiO x is obtained, for example, by heat-treating silicon monoxide and separating it into a SiO2 phase and a fine Si phase by disproportionation reaction.

[0085] The lithium silicate phase may have a composition represented by, for example, the formula: Li 2z SiO 2+z (0 < z < 2). z may be 1 / 2 or 1. The composite particles in which silicon particles are dispersed in the silicate phase can be obtained, for example, by pulverizing and atomizing a mixture of silicate and raw material silicon while stirring with a ball mill or the like, and then heat-treating the mixture in an inert atmosphere. The carbon phase contains, for example, low-crystalline amorphous carbon (amorphous carbon).

[0086] From the viewpoint of improving conductivity, at least a part of the surface of the composite particles may be coated with a conductive layer. The conductive layer contains a conductive material such as conductive carbon. The coating amount of the conductive layer is, for example, 1 part by mass or more and 10 parts by mass or less per 100 parts by mass in total of the composite particles and the conductive layer. The composite particles having a conductive layer on the surface can be obtained, for example, by mixing coal pitch or the like with the composite particles and heat-treating them in an inert atmosphere.

[0087] Compared with graphite particles, Si-based particles have a large capacity, but the degree of expansion and contraction during charging and discharging is large. On the other hand, graphite particles A are hard and difficult to break. Therefore, when the Si-based particles contract due to discharge, gaps are easily formed between the graphite particles A and the Si-based particles. When Si-based particles are used in the negative electrode active material, it is easy to increase the interparticle porosity by including more graphite particles A in the first region than in the second region. When graphite particles and Si-based particles are used in combination, the ratio of Si-based particles in the negative electrode active material (the total of graphite particles and Si-based particles) is preferably 1% by mass or more and 10% by mass or less, more preferably 3% by mass or more and 7% by mass or less. In this case, it is easy to obtain a well-balanced improvement in cycle characteristics and high capacity.

[0088] Examples of the binder include resin materials, such as fluororesins such as polytetrafluoroethylene and polyvinylidene fluoride (PVDF); polyolefin resins such as polyethylene and polypropylene; polyamide resins such as aramid resin; polyimide and polyamideimide; acrylic resins such as polyacrylic acid, polymethyl acrylate, and ethylene-acrylic acid copolymer; vinyl resins such as polyacrylonitrile and polyvinyl acetate; polyvinylpyrrolidone; polyethersulfone; and rubber-like materials such as styrene-butadiene copolymer rubber (SBR). One type of binder may be used alone, or two or more types may be used in combination.

[0089] Examples of the conductive agent include carbons such as acetylene black, conductive fibers such as carbon fibers and metal fibers, metal powders such as aluminum, etc. The conductive agent may be used alone or in combination of two or more.

[0090] Examples of thickeners include carboxymethylcellulose (CMC) and its modified products (including salts such as Na salt), cellulose derivatives such as methylcellulose (cellulose ether, etc.), and saponified polymers having vinyl acetate units such as polyvinyl alcohol, etc. The thickeners may be used alone or in combination of two or more.

[0091] The dispersion medium is not particularly limited, but examples thereof include water, alcohols such as ethanol, ethers such as tetrahydrofuran, amides such as dimethylformamide, N-methyl-2-pyrrolidone (NMP), and mixtures of these.

[0092] As the negative electrode current collector, a non-porous conductive substrate (metal foil, etc.) or a porous conductive substrate (mesh, net, punched sheet, etc.) is used. Examples of the material of the negative electrode current collector include stainless steel, nickel, nickel alloy, copper, copper alloy, etc. The thickness of the negative electrode current collector is not particularly limited, but is preferably 1 to 50 μm, more preferably 5 to 20 μm.

[0093] [Positive electrode] The positive electrode includes, for example, a positive electrode current collector and a positive electrode mixture layer supported on the surface of the positive electrode current collector. The positive electrode mixture layer can be formed by applying a positive electrode slurry in which the positive electrode mixture is dispersed in a dispersion medium to the surface of the positive electrode current collector and drying it. The coating film after drying may be rolled as necessary. The positive electrode mixture layer may be formed on one surface of the sheet-shaped positive electrode current collector or on both surfaces. The positive electrode mixture includes a positive electrode active material as an essential component, and may include a binder, a conductive agent, etc. as optional components. NMP or the like is used as the dispersion medium of the positive electrode slurry.

[0094] As the positive electrode active material, for example, a composite oxide containing lithium and a transition metal such as Ni, Co, or Mn can be used. For example, Li a CoO2, Li a NiO2, Li a MnO2, Li a Co b Ni 1-b O2, Li a Co b M 1-b O c , Li a Ni 1-b M b O c , Li a Mn2O4, Li a Mn 2-b M b O 4、LiMPO 4、 Examples include Li2MPO4F (where M is at least one selected from the group consisting of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, and B). Here, 0 < a ≤ 1.2, 0 < b ≤ 0.9, and 2.0 ≤ c < 2.3. Note that the value of a representing the molar ratio of lithium increases or decreases during charge and discharge.

[0095] Among them, Li a Ni b Me 1-b Lithium nickel composite oxides represented by O2 (where M is at least one selected from the group consisting of Mn, Co, and Al, 0 < a ≤ 1.2, and 0.3 ≤ b ≤ 1) are preferred. From the perspective of increasing capacity, it is more preferable to satisfy 0.85 ≤ b ≤ 1. From the perspective of the stability of the crystal structure, Li a Ni b Co c Al d O2 (0 < a ≤ 1.2, 0.85 ≤ b < 1, 0 < c < 0.15, 0 < d ≤ 0.1, and b + c + d = 1) is even more preferred.

[0096] As the binder and conductive agent, the same ones as those exemplified for the negative electrode can be used. As the conductive agent, graphite such as natural graphite and artificial graphite may be used.

[0097] The shape and thickness of the positive electrode current collector can be selected respectively from the shape and range corresponding to the negative electrode current collector. Examples of the material of the positive electrode current collector include stainless steel, aluminum, aluminum alloy, titanium, etc.

[0098] [Non-aqueous electrolyte] The non-aqueous electrolyte contains a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent. The non-aqueous solvent contains at least one additive selected from the group consisting of sulfite compounds and sulfate compounds.

[0099] Examples of the non-aqueous solvent include cyclic carbonates, chain carbonates, cyclic carboxylates, and chain carboxylates. Examples of the cyclic carbonates include propylene carbonate (PC) and ethylene carbonate (EC). Examples of the cyclic carbonates include cyclic carbonates having an unsaturated bond such as vinylene carbonate (VC). Examples of the cyclic carbonates include fluorine atoms such as fluoroethylene carbonate (FEC). Examples of the chain carbonates include diethyl carbonate (DEC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC). Examples of the cyclic carboxylates include γ-butyrolactone (GBL), γ-valerolactone (GVL), and the like. Examples of the chain carboxylates include methyl formate, ethyl formate, propyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, and propyl propionate. The non-aqueous solvents may be used alone or in combination of two or more.

[0100] Examples of lithium salts include LiClO4, LiBF4, LiPF6, LiAlCl4, LiSbF6, LiSCN, LiCF3SO3, LiCF3CO2, LiAsF6, LiB 10 Cl 10, lithium aliphatic carboxylates, LiCl, LiBr, LiI, borates, imide salts, etc. Examples of borates include lithium bis(1,2-benzenediolate(2-)-O,O')borate, lithium bis(2,3-naphthalenediolate(2-)-O,O')borate, lithium bis(2,2'-biphenyldiolate(2-)-O,O')borate, lithium bis(5-fluoro-2-oleate-1-benzenesulfonic acid-O,O')borate, etc. Examples of imide salts include lithium bisfluorosulfonylimide (LiN(FSO2)2), lithium bistrifluoromethanesulfonate imide (LiN(CF3SO2)2), lithium trifluoromethanesulfonate nonafluorobutanesulfonate imide (LiN(CF3SO2)(C4F9SO2)), and lithium bispentafluoroethanesulfonate imide (LiN(C2F5SO2)2). The lithium salt may be used alone or in combination of two or more. The concentration of the lithium salt in the nonaqueous electrolyte is, for example, 0.5 mol / L or more and 2 mol / L or less.

[0101] [Separator] Usually, it is desirable to interpose a separator between the positive electrode and the negative electrode. The separator has high ion permeability and has appropriate mechanical strength and insulation properties. As the separator, a microporous thin film, a woven fabric, a nonwoven fabric, etc. can be used. As the material of the separator, polyolefin such as polypropylene and polyethylene is preferable.

[0102] An example of the structure of the non-aqueous electrolyte secondary battery is a structure in which an electrode group formed by winding a positive electrode and a negative electrode with a separator interposed therebetween and a non-aqueous electrolyte are housed in an exterior body. Alternatively, instead of a wound type electrode group, an electrode group of another form, such as a stacked type electrode group formed by stacking a positive electrode and a negative electrode with a separator interposed therebetween, may be applied. The non-aqueous electrolyte secondary battery may be in any form, such as a cylindrical type, a square type, a coin type, a button type, a laminate type, or the like.

[0103] FIG. 3 is a schematic perspective view, with a portion cut away, of a nonaqueous electrolyte secondary battery according to one embodiment of the present disclosure.

[0104] The battery includes a bottomed rectangular battery case 4, and an electrode group 1 and a non-aqueous electrolyte contained in the battery case 4. The non-aqueous electrolyte contains at least one additive selected from the group consisting of sulfite compounds and sulfate compounds. The electrode group 1 includes a long strip-shaped negative electrode, a long strip-shaped positive electrode, and a separator interposed between them to prevent direct contact. The electrode group 1 is formed by winding the negative electrode, the positive electrode, and the separator around a flat plate-shaped winding core and removing the winding core.

[0105] One end of the negative electrode lead 3 is attached to the negative electrode collector of the negative electrode by welding or the like. The other end of the negative electrode lead 3 is electrically connected to a negative electrode terminal 6 provided on the sealing plate 5 via a resin insulating plate. The negative electrode terminal 6 is insulated from the sealing plate 5 by a resin gasket 7. One end of the positive electrode lead 2 is attached to the positive electrode collector of the positive electrode by welding or the like. The other end of the positive electrode lead 2 is connected to the back surface of the sealing plate 5 via an insulating plate. That is, the positive electrode lead 2 is electrically connected to the battery case 4 which also serves as the positive electrode terminal. The insulating plate separates the electrode group 1 and the sealing plate 5, and separates the negative electrode lead 3 and the battery case 4. The periphery of the sealing plate 5 is fitted into the open end of the battery case 4, and the fitting portion is laser welded. In this way, the opening of the battery case 4 is sealed with the sealing plate 5. The injection hole for the non-aqueous electrolyte provided in the sealing plate 5 is closed with a sealing plug 8 .

[0106] FIG. 4 is a schematic cross-sectional view showing a negative electrode used in the nonaqueous electrolyte secondary battery of FIG.

[0107] The negative electrode has a sheet-like negative electrode current collector 11 and a negative electrode active material layer 12 having a thickness T formed on both sides of the negative electrode current collector 11. The negative electrode active material layer 12 is divided into two layers, a first region 12a and a second region 12b, each having the same thickness, and the second region 12b is closer to the negative electrode current collector than the first region 12a. That is, the first region and the second region each have a thickness of T / 2. The first region 12a is a half of the negative electrode active material layer 12 on the side opposite to the negative electrode current collector 11 (negative electrode surface side), and the second region 12b is a half of the negative electrode active material layer 12 on the negative electrode current collector 11 side. The first region 12a and the second region 12b each contain graphite particles. The ratio P1 / P2 of the inter-particle porosity P1 of the first region 12a to the inter-particle porosity P2 of the second region 12b is greater than 1.

[0108] The present invention will be specifically described below based on examples and comparative examples, but the present invention is not limited to the following examples.

[0109] <Example 1> [Preparation of graphite particles A] The main raw material, coke (precursor), was pulverized to obtain a pulverized material with an average particle size (D50) of 12 μm. Pitch was added as a binder to the pulverized material to aggregate it, and an aggregate with an average particle size (D50) of 18 μm was obtained. The aggregate was fired at a temperature of 2800°C to be graphitized. The graphitized material obtained was sieved to obtain graphite particles A with an average particle size (D50) of 23 μm.

[0110] [Preparation of graphite particles B] The main raw material, coke (precursor), was pulverized to obtain a pulverized material with an average particle size (D50) of 15 μm. Pitch was added as a binder to the pulverized material to aggregate it, and the aggregate was press-molded to obtain a pulverized material with a density of 1.6 g / cm. 3 ~1.9g / cm 3 The block-shaped molded body was graphitized by firing at a temperature of 2800° C. The graphitized block-shaped body was crushed and sieved to obtain graphite particles B having an average particle size (D50) of 23 μm.

[0111] The internal porosity of graphite particles A was set to 3%. The internal porosity of graphite particles B was set to 15%. The internal porosity of graphite particles A and B was adjusted by the amount of pitch added during the production process of graphite particles A and graphite particles B. Note that the greater the amount of pitch, the greater the intra-particle porosity.

[0112] [Preparation of first negative electrode slurry] An appropriate amount of water was added to the first negative electrode mixture to obtain a first negative electrode slurry. For the first negative electrode mixture, a mixture of the first negative electrode active material, styrene-butadiene copolymer rubber (SBR) as a binder, and carboxymethyl cellulose (CMC) as a thickener was used. For the first negative electrode active material, a mixture of graphite particles A and Si-based particles was used. In the first negative electrode active material, the mass ratio of the graphite particles A to the Si-based particles was 95:5. The mass ratio of the first negative electrode active material to the SBR and CMC was 100:1:1. For the Si-based particles, SiO x The conductive layer was coated with SiO x The amount was 5 parts by mass per 100 parts by mass of the total of the particles and the conductive layer.

[0113] [Preparation of second negative electrode slurry] An appropriate amount of water was added to the second negative electrode mixture to obtain a second negative electrode slurry. The mass ratio of the second negative electrode mixture in the second negative electrode slurry and the mass ratio of the first negative electrode mixture in the first negative electrode slurry were the same. For the second negative electrode mixture, a mixture of the second negative electrode active material, SBR, and CMC was used. For the second negative electrode active material, a mixture of graphite particles B and Si-based particles was used. In the second negative electrode active material, the mass ratio of the graphite particles B to the Si-based particles was 95:5. The mass ratio of the second negative electrode active material to the SBR and CMC was 100:1:1. For the Si-based particles, the same SiO 2 as above was used. x Particles were used.

[0114] [Preparation of negative electrode] The second negative electrode slurry was applied to both sides of the copper foil (thickness 10 μm) serving as the negative electrode current collector, and the second coating was dried. Furthermore, the first negative electrode slurry was applied onto the second coating formed on both sides of the copper foil, and the first coating was dried. The doctor blade method was used to apply the first negative electrode slurry and the second negative electrode slurry. The application amounts of the first negative electrode slurry and the second negative electrode slurry were the same. The application amount of the negative electrode slurry refers to the mass of the negative electrode slurry applied per unit area of ​​the negative electrode current collector.

[0115] The laminate of the dried second coating film and the first coating film was rolled to form a second negative electrode active material layer (thickness: 50 μm, packing density: 1.5 g / cm) on both sides of the negative electrode current collector. 3 ) and the first negative electrode active material layer (thickness: 50 μm, packing density: 1.5 g / cm 3 ) were formed in this order. In this way, a negative electrode was obtained. The first negative electrode active material layer and the second negative electrode active material layer had the same thickness, the first negative electrode active material layer corresponded to the first region, and the second negative electrode active material layer corresponded to the second region. The first negative electrode active material layer was formed by forming the first negative electrode active material (graphite particles A and SiO x particles), and the second negative electrode active material layer contains a second negative electrode active material (graphite particles B and SiO x particles).

[0116] [Preparation of positive electrode] A suitable amount of N-methyl-2-pyrrolidone (NMP) was added to the positive electrode mixture to obtain a positive electrode slurry.

[0117] The positive electrode mixture was a mixture of a lithium-containing composite oxide, which is a positive electrode active material, graphite, which is a conductive material, and polyvinylidene fluoride (PVDF), which is a binder. 0.88 Co 0.09 Al 0.03 In the positive electrode mixture, the mass ratio of the lithium-containing composite oxide, graphite, and PVDF was 100:1:0.9.

[0118] The positive electrode slurry was applied to both sides of an aluminum foil (thickness 15 μm) serving as a positive electrode current collector, and the coating was dried and rolled to form a positive electrode active material layer (density 3.6 g / cm 3The positive electrode slurry was applied by a doctor blade method.

[0119] [Preparation of non-aqueous electrolyte] Ethylene sulfite (ES) and vinylene carbonate (VC) were added as sulfite compounds to a non-aqueous solvent in which ethylene carbonate (EC) and dimethyl carbonate (DMC) were mixed in a volume ratio of 1:3, and LiPF6 was dissolved to prepare a non-aqueous electrolyte. The content of ES in the non-aqueous electrolyte was 1 mass% relative to the entire non-aqueous electrolyte. The content of VC in the non-aqueous electrolyte was 5 mass% relative to the entire non-aqueous electrolyte. The concentration of LiPF6 in the non-aqueous electrolyte was 1.5 mol / L.

[0120] [Preparation of non-aqueous electrolyte secondary battery] An aluminum positive electrode lead was attached to the exposed part of the positive electrode current collector of the positive electrode, and a nickel negative electrode lead was attached to the exposed part of the negative electrode current collector of the negative electrode. Then, the positive electrode and the negative electrode were wound with a separator interposed therebetween to prepare a wound electrode group. A polyethylene microporous film was used as the separator. The electrode group was housed in a battery case. At this time, an upper insulating plate and a lower insulating plate made of resin were arranged above and below the electrode group, respectively. The negative electrode lead was welded to the inner bottom surface of the battery case. The positive electrode lead was welded to a metal sealing body that also served as a positive electrode terminal. Then, a nonaqueous electrolyte was injected into the battery case, and the opening of the battery case was closed using the sealing body. At this time, a resin gasket was interposed between the open end of the battery case and the sealing body. In this way, a cylindrical nonaqueous electrolyte secondary battery (nominal capacity 4600 mAh) was obtained.

[0121] The batteries prepared as above were evaluated as follows.

[0122] [Evaluation 1: Measurement of capacity retention rates A and B at low-rate cycles] In an environment of 25°C, constant current charging was performed at a current of 0.3 C (1380 mA) until the voltage reached 4.2 V, and then constant voltage charging was performed at a voltage of 4.2 V until the current reached 0.02 C. After a 10-minute break, constant current discharging was performed at a current of 0.5 C until the voltage reached 2.5 V. This charge / discharge cycle was counted as one cycle, and 200 cycles were performed, and the discharge capacities at the 1st cycle, 20th cycle, and 200th cycle were calculated. The capacity retention rate A (%) at the 20th cycle was calculated using the following formula to evaluate the initial cycle characteristics.

[0123] Capacity retention rate A = (discharge capacity at 20th cycle / discharge capacity at 1st cycle) x 100 The capacity retention rate B (%) at the 200th cycle was calculated using the following formula to evaluate the medium-term cycle characteristics.

[0124] Capacity retention rate B = (discharge capacity at 200th cycle / discharge capacity at 1st cycle) x 100 In addition, the battery prepared above was separately prepared and subjected to 20 cycles of charge and discharge as in Evaluation 1. Thereafter, the negative electrode was removed from the battery, and the ratio of the interparticle porosity P1 of the first region to the interparticle porosity P2 of the second region: P1 / P2 was determined by the method described above. P1 / P2 was 1.2.

[0125] [Evaluation 2: Measurement of capacity retention rate C at high-rate cycles] In an environment of 25°C, constant current charging was performed at a current of 0.7C (3220mA) until the voltage reached 4.2V, and then constant voltage charging was performed at a voltage of 4.2V until the current reached 0.02C. After a 10-minute break, constant current discharging was performed at a current of 0.5C until the voltage reached 2.5V. This charge / discharge cycle was counted as one cycle, and 50 cycles were performed. The capacity retention rate C (%) was calculated using the following formula to evaluate the high-rate characteristics.

[0126] Capacity retention rate C = (discharge capacity at 50th cycle / discharge capacity at 1st cycle) x 100 <Example 2> A non-aqueous electrolyte secondary battery was produced and evaluated in the same manner as in Example 1, except that ethylene sulfate (DTD) was used as the sulfate compound instead of ES.

[0127] <Example 3> A nonaqueous electrolyte secondary battery was produced and evaluated in the same manner as in Example 1, except that the content of ES in the nonaqueous electrolyte was 0.5 mass % based on the total mass of the nonaqueous electrolyte.

[0128] <Comparative Example 1> The negative electrode slurry was applied to both sides of the negative electrode current collector, the coating was dried and rolled to form a negative electrode active material layer on both sides of the negative electrode current collector, and a negative electrode was obtained. Only the second negative electrode slurry was used as the negative electrode slurry, and the negative electrode active material layer was composed of only the second negative electrode active material layer. The coating amount of the negative electrode slurry was the same as the total coating amount of the first negative electrode slurry and the second negative electrode slurry in Example 1. The thickness of the negative electrode active material layer was the same as the total thickness of the first negative electrode active material layer and the second negative electrode active material layer in Example 1.

[0129] In addition, ES was not added to the non-aqueous electrolyte.

[0130] Except for the above, a non-aqueous electrolyte secondary battery was produced in the same manner as in Example 1 and evaluated.

[0131] <Comparative Example 2> A nonaqueous electrolyte secondary battery was produced and evaluated in the same manner as in Example 1, except that the negative electrode of Comparative Example 1 in which the negative electrode active material layer was composed only of the second negative electrode active material layer was used.

[0132] <Comparative Example 3> A nonaqueous electrolyte secondary battery was produced and evaluated in the same manner as in Example 1, except that ES was not added to the nonaqueous electrolyte.

[0133] The evaluation results are shown in Table 1.

[0134] [Table 1]

[0135] In the batteries of Examples 1 and 3, P1 / P2 was greater than 1 and ES was contained in the nonaqueous electrolyte as a sulfite compound, so that the initial cycle characteristics and high rate characteristics were improved.

[0136] In the battery of Example 2, P1 / P2 was greater than 1, and DTD was contained in the nonaqueous electrolyte as a sulfate compound, so that the initial cycle characteristics and high rate characteristics were improved. In the batteries of Examples 1 to 3, the mid-term cycle characteristics were also improved.

[0137] In the batteries of Comparative Examples 1 and 2, the negative electrode active material layer was composed of one layer, so P1 / P2 was 1, and the high-rate characteristics were deteriorated. In the battery of Comparative Example 3, the negative electrode active material layer was composed of two layers, so the high-rate characteristics were improved compared to the battery of Comparative Example 1, but the initial cycle characteristics were deteriorated compared to the battery of Comparative Example 1 because no additive was added to the nonaqueous electrolyte. [Industrial Applicability]

[0138] The nonaqueous electrolyte secondary battery according to the present disclosure is suitable for use in applications requiring, for example, excellent initial cycle characteristics and high rate characteristics. [Explanation of symbols]

[0139] 1 electrode group 2 Positive Lead 3 Negative lead 4 Battery case 5 Sealing plate 6 Negative terminal 7 Gasket 8. Sealing 11 Negative electrode current collector 12 Negative electrode active material layer 12a 1st area 12b Second area 20 Graphite particles 21 Internal void 22 External void 30 Negative electrode active material layer 31 Negative electrode active material particles 32 Voids between negative electrode active material particles 33 Internal void 34 External gap

Claims

1. The battery includes a positive electrode, a negative electrode, and a non-aqueous electrolyte solution, the negative electrode comprises a negative electrode current collector and a negative electrode active material layer supported on the negative electrode current collector, when the negative electrode active material layer is divided into two layers, a first region and a second region, having the same thickness, the second region is closer to the negative electrode current collector than the first region, the first region and the second region each include graphite particles; A ratio of the inter-particle porosity P1 of the first region to the inter-particle porosity P2 of the second region: P1 / P2 is greater than 1; the non-aqueous electrolyte solution contains at least one additive selected from the group consisting of a sulfite compound and a sulfate compound; The graphite particles include graphite particles A and graphite particles B, The graphite particles A have an internal porosity of 5% or less, The graphite particles B have an internal porosity of more than 5%; the graphite particles A are contained in the first region in a larger amount than the second region.

2. 2. The nonaqueous electrolyte secondary battery according to claim 1, wherein the ratio P1 / P2 is 1.1 or more and 2.0 or less.

3. 3 . The nonaqueous electrolyte secondary battery according to claim 1 , wherein a ratio D1 / D2 of a packing density D1 of the first region to a packing density D2 of the second region is 0.9 or more and 1.1 or less.

4. The first region and the second region each have a density of 1.3 g / cm 3 Above, 2.0g / cm 3 4. The nonaqueous electrolyte secondary battery according to claim 1, having a packing density of:

5. 5. The nonaqueous electrolyte secondary battery according to claim 1, wherein the first region and the second region each contain Si-based particles.

6. 6. The nonaqueous electrolyte secondary battery according to claim 1, wherein the additive comprises at least one selected from the group consisting of ethylene sulfite and ethylene sulfate.

7. 7. The nonaqueous electrolyte secondary battery according to claim 1, wherein the content of the additive in the nonaqueous electrolyte is 0.5% by mass or more and 2% by mass or less with respect to the entire nonaqueous electrolyte.

Citation Information

Patent Citations

  • Nonaqueous electrolyte solution secondary battery

    JP1999073990A

  • Nonaqueous electrolyte and lithium secondary battery using the same

    JP2000082492A

  • Nonaqueous secondary battery, electrode, method of manufacturing nonaqueous secondary battery, and method of manufacturing electrode

    JP2007214038A

  • Carbon material for nonaqueous secondary battery, negative electrode, and nonaqueous secondary battery

    JP2014067638A

  • Electrode active material layer for nonaqueous electrolyte secondary battery, and method for manufacturing the same

    JP2015037008A